The effect of market sentiment on stock performance with profitability as a moderating variable - Hutabarat, Francis; Leri Santoso Hutasoit (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
This study investigates the impact of market sentiment on stock performance, with a particular focus on the moderating role of firm profitability. Utilizing a quantitative causal research design, the analysis is based on a sample of small- and mid-cap companies listed on the Indonesia Stock Exchange from 2020 to 2023. Market sentiment is conceptualized as the collective investor psychology influencing trading behaviors and price movements, while profitability serves as a key financial indicator potentially moderating this relationship. Employing moderated regression analysis, the findings reveal that market sentiment significantly influences stock performance. Moreover, profitability exerts a significant moderating effect, such that the relationship between market sentiment and stock returns varies according to the firm’s profitability level. Specifically, market sentiment positively affects stock performance when profitability is low, but this effect turns negative when profitability is high. These results underscore the importance of integrating financial fundamentals with investor sentiment in explaining stock market dynamics. The study contributes to a deeper understanding of how intrinsic firm characteristics can shape the influence of behavioral factors on investment outcomes, offering practical insights for investors and portfolio managers in emerging markets.